Self-Directed Learning (SDL) Model on Pentigraph Writing Skills Among Primary School Students - Cahyono, Bambang Eko Hari; Maruti, Endang Sri; Arvani, Fida (Profesi Pendidikan Dasar, 2024)
Students' waning interest in writing personal narratives and the rise of readily available online examples have led them to take shortcuts, hindering their creative development. Traditional writing instruction, often limited to theoretical explanations, fails to engage students and lacks innovative strategies. This research investigates the effectiveness of the Self-Directed Learning (SDL) model in improving the pentigraph (three-paragraph) writing skills of fifth-grade students. Employing a quasi-experimental design with a quantitative approach and a Posttest-Only Control Design, the study involved 82 fifth-graders from Taman Kota Elementary School in Madiun, Indonesia. Convenience sampling selected two classes (VB and VC) with 20 students each. Data collection utilized questionnaires, tests, and documentation. Findings revealed a positive impact of the SDL model on students' Indonesian pentigraph writing skills. Through independent learning, students demonstrated improvement, progressing from basic tasks to planning, controlling, and self-assessment. The SDL model empowers students to develop their writing based on their unique learning styles. This research highlights the effectiveness of the SDL approach in enhancing pentigraph writing and student ownership of the learning process